Implementation of an interprofessional education session for postgraduate trainees. Issue 2 (17th November 2022) - Tedder, Amanda C.; Deptola, Amber; Kunz, Kyle; Richter, Sara K.
Abstract: Postgraduate residency training provides an opportunity to acquire and apply skills and behaviors learned through interprofessional education (IPE) sessions. Little data exists regarding the perceptions of resident trainees on benefits and barriers of IPE. In this paper, we describe the development and implementation of a case‐based IPE activity focused on chronic obstructive pulmonary disease management and inhaler technique in order to explore pharmacy and medicine resident perceptions of IPE. Perceptions of IPE were logged via survey and interviews in parallel with participation in the IPE activity and were analyzed with a constructivist grounded theory approach to identify common themes. Four themes supporting IPE models were found including better understanding of another profession's skills, integration of another profession's skill and perspective to improve patient care, recognition of gaps in expertise, and perception of time and coordination as barriers to learning with other professions. In conclusion, IPE activities improve and advance the perceptions and knowledge that medicine and pharmacy residents have about each other's professions.